Pemekaran sebagai arena konflik Ekonomi: Studi kasus Pada rencana pemekaran Provinsi Luwu Raya - Reksa Burhan (Departemen Ilmu Pemerintahan Fisip Unhas, 2020)
Research to answer the question of why pemekaran in Luwu Raya is so complex. The study was conducted in Luwu Raya, South Sulawesi Province. Using qualitative methods with data collection techniques in the form of observation and in-depth interviews. Then analyze the data by elaborating on the results of interviews and secondary data in the form of official government reports (BPS). The results showed that the dynamics and complexity of pemekaran took place in Luwu due to the tug-of-war of the local political elite. Elite tug-of-war takes place in a very open arena, involving various local elites, including political elites and bureaucratic elites. The tug-of-war of the local elite finally makes the agenda of pemekaran that has been normatively determined to be absent from its proper schedule. Field findings also confirm that the division is not only constrained in technical terms. As much is seen from an administrative perspective, but in a political perspective there is something more than that. The author sees it as a matter of local politics. Therefore, the main argument in this study is that the tug-of-war between local political elites is the main cause of the mandate of the pemekaran process that took place in Luwu Raya.